2010
DOI: 10.1093/chemse/bjp105
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Scent-Gland Secretions in an Old World Monkey (Mandrillus sphinx): Influence of Sex, Male Status, and Individual Identity

Abstract: Primates are traditionally considered to be microsmatic, with decreased reliance on olfactory senses in comparison to other sensory modalities such as vision. This is particularly the case for Old World monkeys and apes (catarrhines). However, various lines of evidence suggest that chemical communication may be important in these species, including the presence of a sternal scent-gland in the mandrill. We investigated the volatile components of mandrill odor using gas chromatography-mass spectrometry. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
97
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 82 publications
12
97
4
Order By: Relevance
“…The sex differences that we identified in odour signal diversity build on our previous analyses in which we found that we could reliably discriminate male and female odour profiles using DFA [33], and suggest that sex differences in odour profiles are owing to differences in how the chemical diversity is distributed among the different compounds that comprise the signal, rather than to differences in the number of compounds present. This provides an interesting comparison with ring-tailed lemurs, where female odour contains more compounds than male's [28], and reflects differences in the social system of the two species.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The sex differences that we identified in odour signal diversity build on our previous analyses in which we found that we could reliably discriminate male and female odour profiles using DFA [33], and suggest that sex differences in odour profiles are owing to differences in how the chemical diversity is distributed among the different compounds that comprise the signal, rather than to differences in the number of compounds present. This provides an interesting comparison with ring-tailed lemurs, where female odour contains more compounds than male's [28], and reflects differences in the social system of the two species.…”
Section: Discussionsupporting
confidence: 71%
“…We retained PCs with eigenvalues greater than 1 (15 PCs for swabs, explaining a total 79.3% of the variance; 18 PCs for hair samples, explaining a total 76.8% of the variance; [33]). We used these PCs as covariates in discriminant function analysis (DFA) to examine the relationship between odour and MHC genotype, grouping samples using possession of individual supertypes (present/absent for each).…”
Section: (D) Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, a resurgence of interest in primate olfactory capacities provides further support for the idea that chemical cues play a role in communication in all major primate radiations [49,53,54]. Analyses of the content of chemical signals suggest that they can advertise individual traits in ring-tailed lemurs [42], mandrills [55] and humans [56]. Moreover, odour signals genome-wide diversity and genetic relatedness in ringtailed lemurs [42,57] and mandrills [58], as well as MHC diversity and dissimilarity in mandrills [58].…”
Section: There Are No Global Patternsmentioning
confidence: 87%
“…For example, colour in mandrills is part of a suite of visual, olfactory and acoustic traits (Darwin, 1871;Osman Hill, 1970). While male mandrill colour and odour both signal age and rank, they also reflect different aspects of the male: red signals testosterone and some MHC genotypes, while odour encodes genetic diversity and genetic similarity (Setchell et al, 2011(Setchell et al, , 2009Setchell, Vaglio, et al, 2010). Similarly, red colour and barks in male rhesus macaques have the potential to convey different information to the perceiver (Higham et al, 2013).…”
Section: Discussionmentioning
confidence: 99%